The Use of Technology in Increasing Religious Knowledge of Early Childhood (Current Research in Education: Conference Series Journal, 2024)
Religious knowledge in early childhood has an important role in shaping their moral and ethical values. The utilization of technology has become one of the effective tools in improving religious understanding in early childhood. The purpose of this research is for literature and library studies on the utilization of technology to increase knowledge of Islamic religion for early childhood, as a reference for teachers and parents of children in utilizing technology as an increase in knowledge. The assessment method is carried out by referring to literature studies on relevant research results. Previous studies also highlight that digital media such as animations, videos, and interactive learning tools can make religious material more engaging and easier for young children to understand. Technology is also noted to provide wider access to Islamic learning resources, allowing children to learn anytime with proper guidance from adults. The results of the discussion in the study are how technology in the view of Islam, the introduction of Islam for early childhood, the utilization of technology in learning religion for early childhood, and the advantages and disadvantages of technology for early childhood.